Correctness of the radiation creep equations that involve the stress and accumulated irreversible deformation in the model of radiation swelling of an irradiated material - Chirkov, O.Yu. (Reports of the National Academy of Sciences of Ukraine, 2021)
The results of the correctness analysis of the determining equations of radiation creep are presented, which allow one to describe the non-isothermal processes of inelastic deformation with regard for the radiation swelling and radiation creep of a material under conditions of neutron irradiation, high temperatures, and damaging dose. Modern models of radiation swelling and radiation creep are considered, which involve the damaging dose, irradiation temperature and the influence of a stress and an accumulated irreversible deformation on the processes of radiation swelling and radiation creep of the material. Based on the general results of the analysis of the properties of nonlinear operators, the conditions that ensure the correctness of the formulated equations of radiation creep are determined. According to the results of the analysis, it is established that the consideration of the accumulated irreversible deformation in the model of compressed swelling helps one to relax the restrictions on a possible swelling of the material and the initial data that ensure the correctness of the determining equations of radiation creep.